Organizational Development within The Palm Oil Industry: The Application of Occupational Health and Safety (OHS) - Waldan, Raziki; Ruci, Dewa (Faculty Of Islamic Economics and Business, 2025)
Purpose: This article aims to analyze the implementation of Occupational Health and Safety (OHS) in organizational development at PT. Enggang Mill, a palm oil industry company. The primary focus of this study is to evaluate the company's policies, procedures, training, and efforts in fostering a safety culture, as well as to identify challenges in achieving a zero-incident environment.Method: The methodology involves direct interviews with Mr. Adrian Syah, the Head of Safety at PT. Enggang Mill, and an analysis of the OHS policies and procedures in place. The collected data are analyzed qualitatively to understand the effectiveness and challenges in the execution of OHS programs within the factory setting.Research Findings: The findings reveal that PT. Enggang Mill has implemented stringent safety policies and procedures, including regular training, provision of personal protective equipment (PPE), and the installation of warning signs throughout the work areas. However, the greatest challenge remains in cultivating a safety culture among employees, where further efforts are needed to enhance awareness and compliance with OHS procedures. The implications of this research emphasize the importance of management support and active employee participation in creating a safe and productive work environment. The novelty of this study lies in its comprehensive approach, combining an evaluation of safety policies with an analysis of safety culture within the company, providing insights into how safety culture can be a decisive factor in the success of OHS programs. Tujuan Penelitian: Artikel ini bertujuan untuk menganalisis penerapan Kesehatan dan Keselamatan Kerja (K3) dalam pengembangan organisasi di PT. Enggang Mill, sebuah perusahaan industri kelapa sawit. Fokus utama dari studi ini adalah untuk mengevaluasi kebijakan, prosedur, pelatihan, dan upaya perusahaan dalam membangun budaya keselamatan, serta mengidentifikasi tantangan dalam mencapai lingkungan tanpa insiden.Metode: Metode yang digunakan melibatkan wawancara langsung dengan Bapak Adrian Syah, Kepala Kesehatan dan Keselamatan di PT. Enggang Mill, serta analisis kebijakan dan prosedur K3 yang diterapkan. Data yang dikumpulkan dianalisis secara kualitatif untuk memahami efektivitas dan tantangan dalam pelaksanaan program K3 di lingkungan pabrik.Temuan Penelitian: Temuan menunjukkan bahwa PT. Enggang Mill telah menerapkan kebijakan dan prosedur keselamatan yang ketat, termasuk pelatihan rutin, penyediaan alat pelindung diri (APD), dan pemasangan tanda peringatan di seluruh area kerja. Namun, tantangan terbesar tetap pada pembentukan budaya keselamatan di antara karyawan, di mana perlu ada upaya lebih lanjut untuk meningkatkan kesadaran dan kepatuhan terhadap prosedur K3. Implikasi dari penelitian ini menekankan pentingnya dukungan manajemen dan partisipasi aktif karyawan dalam menciPT.akan lingkungan kerja yang aman dan produktif. Kebaruan dari studi ini terletak pada pendekatannya yang komprehensif, menggabungkan evaluasi kebijakan keselamatan dengan analisis budaya keselamatan di dalam perusahaan, memberikan wawasan tentang bagaimana budaya keselamatan dapat menjadi faktor penentu dalam keberhasilan program K3.